PENGARUH PEMBERIAN KUNYIT DAN TEMULAWAK MELALUI AIR MINUM TERHADAP TITER ANTIBODY AI, IBD, DAN ND PADA BROILER - Dani Rohmad Nurkholis; Syahrio Tantalo; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The objective of this research is to know the influence of using turmeric and curcuma toward antibody titer AvianInfluenza (AI), Infectious Bursal Desease (IBD), and Newcastle Desease (ND) at broiler. This research isimplemented from February--March 2013 at PT. Rama Jaya Lampung experiments shed in Fajar Baru II village, JatiAgung Sub-district, South Lampung regency. The chicken that used is broiler rooster strain Cobb as much as 180head. This research is implemented by using Complete Random Design (CRD) with three treatment and sixrepetition. The treatment that used is regular water (P0); turmeric stew water 10 g/600 ml (P1); and curcuma stewwater 10 g/600 ml (P2). Taking of blood sample is implemented as much as 20% from total unit experiment. Thedata from this research is tested by using descriptive test. The mean of antibody titer Avian Influenza that producedafter 20 days vaccination is P0 (0,33 log 2), P1 (0,17 log 2), and P2 (0, 17 log 2). The mean of antibody titerInfectious Bursal Desease that produced after 15 days vaccination is P0 (6.400,92), P1 (4.391,43), and P2(5.098,50). The mean of antibody titer Newcastle Desease that produced after 20 days vaccination is P0 (4,42 log 2),P1 (4,42 log 2), and (5,00 log 2). The result of this research shows that by giving turmeric stew water have notpositive influence toward antibody titer Avian Influenza, Infectious Bursal Desease, and Newcastle Desease (P1lower than P0), meanwhile by giving curcuma have not positive influence toward antibody titer Avian Influenza andInfectious Bursal Desease (P2 lower than P0), but have positive influence toward antibody titer Newcastle Desease(P2 higher than P0).